Cross-linguistic interaction in third language learning - Szabó Noémi („RIK-U” Kft., 2018)
Abstract. In the Dynamic Model of Multilingualism (Herdina and Jessner 2002) new emergent skills, that is language learning skills, language management skills, and language maintenance skills characterize the multilingual repertoire. These proficiency skills are strongly related to multilingual awareness which is divided into metalinguistic and cross-linguistic awareness (Jessner 2006). Cross-linguistic awareness deserves more attention in consideration of third language acquisition and trilingualism because this area of research is still counted as a neglected area in multilingualism research.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: third language; cross-linguistic interaction